The vulnerability of heterosexuality: Consent, gender deception and embodiment - Travis, Mitchell (Social and Legal Studies)
This article considers the institutional frameworks that privilege heterosexuality, police notions of sex and gender and individualize discussions and responsibilities around consent. In doing so, Vulnerability theory is drawn upon and added to through the introduction of a richer conception of embodiment. By understanding embodiment as a product of corporeality, discourse and institutions, vulnerability theory is better equipped to engage with the complexities of LGBTIAQ identities. The article traces these developments by engaging with a series of recent criminal law cases concerning deception as to gender. It then reflects upon the ways in which institutions such as law, the family and educational systems focus on individualizing responsibilities around consent rather than focusing on their own role in creating the conditions under which non-heterosexual sex is disincentivized, constructed as predatory and ultimately criminalized. It concludes by demanding a new approach from the state that moves away from carceral approaches towards educative programmes grounded in substantive equality. - Reproduced.
Keywords: Lesbians; LGBTIAQ; Heterosexuality; Gender